Specific Time Work Agreement (PKWT) After the Constitutional Court Ruling No. 168/PUU.XXI/2023, Is It Still Relevant? - Abraham Pierre Wenang P; Al Arif Nur Siregar; Cindy Patricia Galag; Grace Grace; Hasoloan Sinaga (Jurnal Indonesia Sosial Sains, 2025)
The Constitutional Court (MK) decision number 168/PUU-XX1/2023 has a major impact on the world of employment and the business world where the Indonesian economy is facing pressure and slowdown due to global economic challenges. Even during the last few months in mid-2024, there has been a deflationary trend that shows a decline in people's purchasing power, which has a major impact on domestic consumption. This condition directly affects various business sectors, especially labor-intensive industries that have a great dependence on national economic stability. Moreover, there are still industries that have not recovered from the impact of Covid-19 in 2020-2021. The author tries to analyze the legal consequences and their social and commercial impact on the Constitutional Court's Decision on the Fixed-Time Work Agreement (PKWT) which can only be a maximum of 5 (five) years, which includes the extension period of the employment agreement.